2016
DOI: 10.1007/s00330-015-4178-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased fractional anisotropy in the motor tracts of Parkinson's disease suggests compensatory neuroplasticity or selective neurodegeneration

Abstract: ObjectiveTo determine the differences in motor pathways and selected non-motor pathways of the basal ganglia in Parkinson’s disease (PD) patients compared to healthy controls (HCs).MethodsWe analysed diffusion weighted imaging data of 24 PD patients and 26 HCs. We performed deterministic tractography analysis using the spherical deconvolution-based damped Richardson-Lucy algorithm and subcortical volume analysis.ResultsWe found significantly increased fractional anisotropy (FA) in the motor pathways of PD pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
86
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 33 publications
12
86
0
Order By: Relevance
“…In PD, it has been widely used in evaluating structural changes in the substantia nigra, but its applications are not restricted to subcortical structures. Reduced FA was detected in the precentral gyrus and SMA in PD, whereas another study assessing diffusion MRI changes across motor tracts found increased FA in the corticospinal and thalamus‐motor cortex tracts in patients when compared with controls . These rather unexpected findings highlight the possibility of microstructural changes being far more extensive than previously thought, encompassing complex pathways involved in the initiation and control of movement.…”
Section: Structural Changes In the Motor Cortex Of Pdmentioning
confidence: 76%
“…In PD, it has been widely used in evaluating structural changes in the substantia nigra, but its applications are not restricted to subcortical structures. Reduced FA was detected in the precentral gyrus and SMA in PD, whereas another study assessing diffusion MRI changes across motor tracts found increased FA in the corticospinal and thalamus‐motor cortex tracts in patients when compared with controls . These rather unexpected findings highlight the possibility of microstructural changes being far more extensive than previously thought, encompassing complex pathways involved in the initiation and control of movement.…”
Section: Structural Changes In the Motor Cortex Of Pdmentioning
confidence: 76%
“…These metrics, therefore, provide complementary information about microstructural damage. Considering them in combination in MS, as well as in other conditions affecting the integrity of white matter (Mole et al, ), can improve our understanding of tissue pathology and may offer more accurate measurement of the effect of novel therapeutic interventions for prevention, neuroprotection or repair.…”
Section: Discussionmentioning
confidence: 99%
“…It is common to report asymmetry or group difference in bundle volume (Catani et al, 2007;Chenot et al, 2019;Song et al, 2014), diffusion values within the bundle of interest (average fractional anisotropy, mean diffusivity, etc.) (De Erausquin & Alba-Ferrara, 2013;Kimura-Ohba et al, 2016;Ling et al, 2012;Mole et al, 2016) or values along the bundle (called profilometry and tractometry) (Cousineau et al, 2017;Dayan et al, 2016;Yeatman, Dougherty, Myall, Wandell, & Feldman, 2012;Yeatman, Richie-Halford, Smith, Keshavan, & Rokem, 2018). Spatial distribution of cortical terminations of streamlines can help to identify cortical regions with underlying WM connections affected by a condition (Behrens et al, 2003;Donahue et al, 2016;Johansen-Berg et al, 2004;Mars et al, 2011;Rushworth, Behrens, & Johansen-Berg, 2005).…”
Section: Bundle Segmentationmentioning
confidence: 99%